Autoimmune hepatitis under the COVID-19 veil: an analysis of the nature of potential associations - Yu, Chaojie; Wang, Wenrui; Zhang, Qian; Jin, Zhenjing (Frontiers in Immunology, 2025)
In recent years, the novel coronavirus infectious disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has led to over 670 million infections and nearly 7 million deaths worldwide. The global pandemic of COVID-19 has precipitated a significant public health crisis. The prevalence of liver function abnormalities associated with SARS-CoV-2 is as high as 53% among healthy individuals or patients with autoimmune hepatitis (AIH) and shows a positive correlation with disease severity; moreover, specific adaptive immune responses can influence the trajectory and outcomes of COVID-19. For instance, SARS-CoV-2 may impact autoimmunity through mechanisms such as excessive stimulation of immune responses and molecular mimicry, particularly in genetically predisposed individuals. Currently, the overall mutational trend of SARS-CoV-2 indicates heightened infectivity and immune evasion capabilities. Consequently, vaccination remains crucial for universal protection against this disease. Nevertheless, alongside the widespread implementation of vaccination programs globally, an increasing number of cases have been documented where COVID-19 vaccination appears to trigger new-onset autoimmune hepatitis; yet definitive evidence is still pending elucidation regarding causality. In this review, we analyse the clinical-immunological characteristics, risks associated with severe disease progression, and prognosis for AIH patients infected with SARS-CoV-2; discuss the detrimental effects exerted by SARS-CoV-2 on hepatic function; summarise the mechanisms and attributes leading to new-onset AIH; as well as provide insights into how vaccination may interfere with autoimmunity processes. We continue to underscore the significance of vaccination while aiming to enhance awareness concerning potential risks associated with it—this could facilitate better management strategies for autoimmune diseases along with appropriate adjustments in vaccination protocols. Although the precise triggering mechanism linking COVID-19-related events to AIH remains unclear, existing evidence suggests that this relationship is far from coincidental.